A251 TC-325 USE IN MALIGNANT UPPER GASTROINTESTINAL BLEEDS: A MULTICENTRE RETROSPECTIVE STUDY. (1st March 2018) - Marr, K J; Meng, Z; Mohamed, R; James, P D
Abstract: Background: TC-325 has recently been proposed as a potential therapeutic agent for use in traditionally difficult to treat malignant upper gastrointestinal bleeds (UGIB). Aims: The aim of this study is to assess the proportion of patients with malignant UGIB treated with either TC-325 alone or in combination with conventional therapy that achieve long-term hemostasis. Methods: This is a multicentre retrospective study at the University of Calgary and University of Ottawa assessing the efficacy of TC-325 in achieving hemostasis in malignant UGIB between January 1, 2010 and July 30, 2016. TC-325 use was identified via staff polling, product order forms, and endoscopic records review. Once identified, patient charts and online records (Sunrise Clinical Manager, Calgary; vOACIS, Ottawa) were reviewed to identify those with malignant UGIB and to assess our primary and secondary endpoints. The primary outcome was hemostasis at 7 days. Secondary outcomes include immediate hemostasis, the need for repeat endoscopy, surgical intervention, transarterial embolization, and 30-day mortality. Results: TC-325 was utilized for malignant UGIB in 19 patients. The median age was 68 (IQR 57–78), 11 were males (58%). Fifteen patients (79%) were Forrest Classification 1B with a median Blatchford score of 11 (IQR 7–12). TC-325 was utilized as the primary modality for hemostasis in 15 patients (79%). Eighteen patients (95%) achieved immediate hemostasis post-TC-325 and 8 patients (42%) eventually rebled after this. Three patients (16%) had recurrent bleeding within 24 hours. Only 13 patients had sufficient data to examine our primary endpoint of 7 days and 4 (31%) rebled by that time (all in Calgary). Three patients died before 7 days and 3 changed their goals of care. At 14 days, 3 patients (25%) rebled. A repeat endoscopy was required in 7 patients (37%). Two patients (11%) required surgical intervention. Transarterial embolization was not required. Ten patients died by 30 days (53%); one due to perforation of their malignant ulcer and another from an uncontrollable malignant UGIB. There were no complications directly associated with TC-325. Conclusions: This is the first multicenter study evaluating 7-day hemostasis when TC-325 is used in malignant UGIB. TC-325 is effective at immediate and early hemostasis. However, rebleeding risk is increased by day 7 post-treatment. TC-325 may be utilized to immediately achieve hemostasis. Up to a third of patients may require another definitive intervention to achieve long-term hemostasis. Funding Agencies: None